2007
DOI: 10.1021/jp067669y
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of iR-Free Individual-Electrode Overpotentials in Polymer Electrolyte Fuel Cells

Abstract: A method of measuring error-free potentials of individual electrodes directly in the polymer electrolyte fuel cell and under a full range of load is introduced. Successful measurement is accomplished by placing a reference electrode in ionic contact with the active layer of a fuel cell electrode of interest, that is, away from the electrolyte membrane. Half-cell measurements with the proposed reference electrode configuration are compared with measurements in two other fuel-cell reference electrode arrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…Constant current operation is less desirable as potential changes of more than 0.4-0.5 V for H 2 S [29,[33][34][35] and 0.3 V for SO 2 [30] were observed. Preferably, a reference electrode should be considered but implementation is not necessarily trivial [44] especially if the additional requirement of contaminant insensitivity is added. The ionomer is permeable to contaminants such as H 2 S [16,45] and SO 2 [46].…”
Section: Contamination Mechanismmentioning
confidence: 99%
“…Constant current operation is less desirable as potential changes of more than 0.4-0.5 V for H 2 S [29,[33][34][35] and 0.3 V for SO 2 [30] were observed. Preferably, a reference electrode should be considered but implementation is not necessarily trivial [44] especially if the additional requirement of contaminant insensitivity is added. The ionomer is permeable to contaminants such as H 2 S [16,45] and SO 2 [46].…”
Section: Contamination Mechanismmentioning
confidence: 99%
“…The amplitude of the sinusoidal modulation voltage did not exceed 10 mV. To resolve the anode and cathode impedance, an Ag/AgCl electrode (MF-2052, BAS Inc.) was placed at the region of constant potential (RCP) [32][33][34][35][36] of the membrane as a reference electrode. The detailed description of the setup of reference electrode was proposed and demonstrated in our previous work [32].…”
Section: Operating Conditions and Electrochemical Measurementmentioning
confidence: 99%
“…The electrochemical characterization of thin solid electrolyte fuel cells, for example, showed that results were RE position dependent and prone to errors (Fiaud et al, 1987;Hsieh et al, 1997;Piela et al, 2007;Winkler et al, 1998;Zeng et al, 2010). When the RE is placed in a region of nonuniform current density, the RE can possibly sample a range of equipotential surfaces, resulting in the discrepancies in the measurements (Hsieh et al, 1997).…”
Section: Introductionmentioning
confidence: 99%